Breakthrough in improvement of environment and forest ecosystem through rehabilitation of mines and reclamation of biodiversity in iron ore mines at Bellary sector of Karnataka India. - Singh I.F.S, Dr.U.V. (European Journal of Applied Sciences, 2021)
Mining is one of most destructive red industry responsible for degradation of all major components of the environment i.e. land, water, and air. The illegal mining coupled with excess illegal extraction of iron ore fueled to pollute the environment of Bellary sector during the first decade of this millennium. After series of investigations and reports, the Hon’ble Supreme Court of India took the cognizance and directed State Government to rehabilitate and reclaim the mining leases which are under operation/inactive. The task of preparation of rehabilitation and reclamation plans (R&R Plans) of all mines of iron ore in the Bellary sector was assigned to Indian Council of Forest Research and Education, Dehradun. The monitoring committee appointed by the Hon’ble Supreme Court was requested to monitor the implementation of R&R Plans. The author is one of the members of the three-member Committee. Various engineering structures for rehabilitation and biological measures for reclamation of biodiversity have been discussed in this article. Overall an area of about 10913.00ha. of 166 mines at the cost of Rs. 362.83 crores have been rehabilitated. Photographs of various works carried out in mines have been displayed. The implementation of R&R Plans is the milestone in overall improvement of environment in the history of mining sector. The environment, state of mining, illegalities, investigation and rehabilitation works as discussed in this article for Bellary sector is a result of direct contribution of the author for eighteen years.